The left-handed twin - Perry, Thomas, 1947- (Perry, Thomas, 1947- Jane Whitefield novel, 2021)
When she agrees to help a woman escape a crazed ex-boyfriend who is friends with members of a Russian organized crime brotherhood, rescue artist Jane Whitefield leads a deadly crime syndicate on a wild chase through the Northeast from which only one party--Jane or her pursuers--will emerge alive.